2006
DOI: 10.1007/s10544-006-6377-7
|View full text |Cite
|
Sign up to set email alerts
|

Biorelevant mesoporous silicon / polymer composites: directed assembly, disassembly, and controlled release

Abstract: We describe in this account a general, yet facile strategy for the directed assembly of bioactive composite materials comprised of an erodible organic polymer such as polycaprolactone and physiologically-resorbable inorganic mesoporous silicon. This method exploits a combination of capillary forces and selective interfacial coupling chemistry to produce isolable macroscale (mm sized) structures possessing a diverse range of geometries through simple mixing rather than intricate molding processes. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 30 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…Porous Si composites show great promise for improving the mechanical stability and control over release rates of a delivery system. Polymers that have been incorporated into porous Si include polylactide [146], polydimethylsiloxane [147], polyethylene [146], polystyrene [146], polycaprolactone [148], zein (a biopolymer derived from maize) [149], and poly(N-isopropylacrylamide) [150]. Either the composite itself or a nanostructure derived from the composite by removal of the porous Si template can be used (Fig.…”
Section: Porous Si As a Templatementioning
confidence: 99%
“…Porous Si composites show great promise for improving the mechanical stability and control over release rates of a delivery system. Polymers that have been incorporated into porous Si include polylactide [146], polydimethylsiloxane [147], polyethylene [146], polystyrene [146], polycaprolactone [148], zein (a biopolymer derived from maize) [149], and poly(N-isopropylacrylamide) [150]. Either the composite itself or a nanostructure derived from the composite by removal of the porous Si template can be used (Fig.…”
Section: Porous Si As a Templatementioning
confidence: 99%
“…Actually, it was observed that depending on the porosity and pore size, PSi could be bioinert, bioactive or biodegradable 20. Since then, the issues of bioactivity and biocompatibility of PSi have been intensively studied and very interesting results reported 21–31. For example, the speed of dissolution of PSi depends on the porosity and pore size, and it can be predicted and controlled with fabrication parameters 20, 27.…”
Section: Fabrication and Characterization Of Porous Silicon Materialsmentioning
confidence: 99%
“…PSi could also be used as a material for composite structures. Mukherjee et al165 combined PSi and polycaprolactone to produce biorelevant PSi/polymer composites. Li et al166 prepared polymer replica of PSi using PSi pore network.…”
Section: Drug Delivery Applications Of Porous Silicon Materialsmentioning
confidence: 99%
“…However, if it is combined with biopolymers, it works as the substrate of composite materials providing new advantageous chemical and physical characteristics, which are not exhibited by the individual constituents, such as an improved control over drug release kinetics and improved stability in aqueous solution [48]. Biopolymers that have been incorporated into nanoPS for drug-delivery applications include [48,52,53] polylactide, polydimethylsiloxane, polyethylene, polystyrene, polycaprolactone, poly(N-isopropylacrylamide) and, more recently, b-cyclodextrin-citric acid polymer [54]. Reprinted with permission from [37].…”
Section: Nanops In Drug-delivery Systemsmentioning
confidence: 99%